Multidisciplinary care standard for a ventilated mechanic patient at home in Poland - Grzegorz Ulenberg; Anna Grabowska-Gaweł; Agata Ulenberg; Łukasz Czapiewski; Paulina Smyk; Anna Lewandowska (Kazimierz Wielki University, 2017)
The theoretical considerations on the role of breathing were already carried out by the ancient Egyptians and Greeks. However, the first instrumental attempts to conduct artificial ventilation appeared only in the sixteenth century, when court physician Louis XIV Andreas Vesali Vesalius described the "action of air" blown into the airways of the dog by a reed placed in the trachea. German engineer Heinrich Drager developed a device in 1909 that allowed him to blow air into the patient's airways through a metal mask. The pulmotor, as this respirator was manufactured by Drager Werk AG, allowed the generation of positive pressure in the airways. Before 2000, home-made mechanical de-agglomeration in Poland should be considered as episodic. It was not until 2001 that the Home Care Ventilator Team was launched in the Regional Palliative Care Team in Bydgoszcz. It was the first unit of this type in Poland massively introducing domestic non-invasive ventilation. Currently, there are about 40 centers in Poland, including university units, non-university hospitals and private entities.